Inflammation: purposes, mechanisms and development - Ghezzi, Pietro (Henry Stewart Talks, 2022)
Inflammation as a component of innate immunity, Pathogen-Associated Molecular Patterns and their receptors, Leukocyte infiltration, The hallmarks of inflammation, Systemic effects of inflammation and acute-phase response, Inflammation as a response to injury, Damage-Associated Molecular Patterns, Resolution of inflammation, Regulation of inflammation by adaptive immunity, Chronic Inflammation